THE ROLE OF CIVIL SERVICE POLICE UNIT IN ENFORCING HYGIENE LAWS IN PALU CITY, CENTRAL SULAWESI - Gaghauna, Vanessa Gloria; Tan, Anselmus (Fakultas Hukum Tata Pemerintahan, 2024)
The increase in the population of Palu City has implications for increasing community activities and affecting waste generation, if it cannot be managed properly it will cause various problems. The regulations issued by the Palu City government which prohibit people from littering are often ignored. This research aims to analyze and describe the role of the Palu City Satpol-PP in enforcing regional legal products regarding waste management and cleanliness by identifying and analyzing supporting and inhibiting factors, as well as what efforts are being made. This research employed a descriptive method with a qualitative approach. Data collection techniques were conducted through interviews, observations, and document studies. The results of this research show that the Palu City Civil Service Police Unit has carried out its role well as a regional law enforcer regarding cleanliness, in this case, its role as a stabilizer, innovator, modernizer, and pioneer. However, there are still several obstacles, including a lack of public awareness and limited Civil Servant Investigator personnel. Thus, the Palu City Civil Service Police Unit is intensively carrying out outreach and counselling to the community and business actors, taking a humanist and persuasive approach, as well as increasing the number of Civil Servant Investigators.